2022
DOI: 10.1037/emo0000843
|View full text |Cite
|
Sign up to set email alerts
|

Physical and social anhedonia in female adolescents: A factor analysis of self-report measures.

Abstract: Anhedonia is a transdiagnostic symptom of psychopathology that includes diminished positive emotions and anticipation and enjoyment of reward, with particular salience during adolescence. However, the construct validity of anhedonia dimensions is not well established, thus limiting operationalization and generalization of the construct. We applied exploratory and confirmatory factor analyses to identify latent dimensions of anhedonia across four commonly used self-report measures covering different facets of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 126 publications
(177 reference statements)
0
4
0
Order By: Relevance
“…Additionally, both males and females reported similar preferences for hobbies (e.g., watching short videos), food/drink (e.g., fried foods), and sensory experiences (e.g., listening to music). Moreover, the DARS measured the participants’ state of anhedonia ( 19 ), and studies focusing on adolescent state of anhedonia did not report significant sex differences ( 20 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both males and females reported similar preferences for hobbies (e.g., watching short videos), food/drink (e.g., fried foods), and sensory experiences (e.g., listening to music). Moreover, the DARS measured the participants’ state of anhedonia ( 19 ), and studies focusing on adolescent state of anhedonia did not report significant sex differences ( 20 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the speed of social change and the current COVID 19 pandemic are similar in terms of affecting human behavior all over the world [8,22,23,24]. When the literature on the subject is examined, it is possible to come across studies that reveal the effects of the mentioned social events on various social groups [13,25]. However, when the relevant studies were reviewed, no research was found in which the sample group consisted of students studying in the field of sports.…”
Section: Original Articlementioning
confidence: 99%
“…It has been known for decades that anhedonia is a heterogenous construct and can be decomposed into physical and social anhedonia ( Chapman et al., 1976 ), and this two-dimensional structure of anhedonia has been validated among both non-clinical and clinical individuals ( Langvik & Borgen Austad, 2019 ; Yang et al., 2022 ). Physical anhedonia is associated with decreased pleasure for physical or sensory experiences, whereas social anhedonia involves deriving less pleasure from social interaction with other people.…”
Section: Introductionmentioning
confidence: 99%